The Old Testament use of the Law : the oldest perspective of Paul / - Tolliver, Mike, 1983- (2013)
1 online resource (1 PDF (ix, 121 leaves)); Typescript; Includes abstract; Thesis (Th. M.)--Covenant Theological Seminary, 2013; Bibliography: leaves 117-121